(untitled) - Akhand, Hafiz A. (London, UK, 2006)
During the period 1965 to 1990 East Asia was the world's fastest growing region. Economic Development in Pacific Asia provides illuminating, non-technical perspectives on key facets of the region's economies. The text focuses on the eight countries which accounted for the majority of the economic growth; Japan, Hong Kong, Taiwan, Republic of Korea, Indonesia, Malaysia, Singapore and Thailand.Empirical evidence is used to provide a revealing, multi-dimensional statistical profile of the countries as well as the region as a whole. Rather than present a statistical history of each country, the text highlights the relative performance in terms of the variables which are studied within each chapter. Akhand and Gupta examine a range of popular topics including:- the relative role of factors accumulation versus technology change- factor price distribution and employment- growth, poverty and income distribution- the Asian Crisis and corruption.In addition, the book examines topics rarely covered in the current economics literature such as urbanization, the gender gap and the digital divide. It provides an accessible and wide ranging assessment of the existing evidence and current arguments on East Asian economic development, and will be a valuable addition to economists, policy makers and those interested in Asian economic affairs.
Keywords: East asia,Southeast asia; Economic conditions,Economic conditions